2018
DOI: 10.35808/ersj/1243
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bounded Consumers' Rationality Based on Micro Segmentation

Abstract: The relevance of the study is due to the need to optimize the procedures for identifying the target audience online. In this regard, the article is aimed at identifying the benefits of finding the target audience for the subsequent promotion of the product through streaming micro-segmentation of network users. Orientation of the marketing company at the potential consumer significantly increases the cost effectiveness. However, society responds to this by forming a limited rationality in the behavioral aspect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Conducting an experiment can be very costly, it will most likely take quite a long time to complete, and after the experiment is over, the time to make decision may be lost. In addition, it is rather difficult to conduct experiments in economics due to the uniqueness of each situation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Conducting an experiment can be very costly, it will most likely take quite a long time to complete, and after the experiment is over, the time to make decision may be lost. In addition, it is rather difficult to conduct experiments in economics due to the uniqueness of each situation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical and methodological basis of the research includes the established scientific methods, works of Russian scholars (Balalova et al 2021;Bessonov and Suglobov 2019;Dudukalova et al 2020;Kontsevaya et al 2020;Maksaev et al 2021;Maloletko et al 2021;Mityushina et al 2017;Nabiyeva 2021;Orlova et al 2020;Rodionov et al 2020;Shinkareva et al 2021;Starodubtseva et al 2021;Volkov et al 2018), and recommendations of research institutions on this topic. The assessment of the current level of operating forms of the dairy complex involves methods of knowledge, analysis, and synthesis, as well as monographic and abstract-logical methods.…”
Section: Methodsmentioning
confidence: 99%
“…In real life, when communicating with a consultant who has experience in teaching sales techniques, during the dialogue it would be revealed that a particular brand is interested in a particular consumer and a blind offer will not have an effect. Therefore, in this case, feedback from the consumer is needed to create a network user profile with certain criteria and marks [18,19].…”
Section: Literature Reviewmentioning
confidence: 99%